2013
DOI: 10.1088/0031-8949/88/03/035002
|View full text |Cite
|
Sign up to set email alerts
|

Performance characteristics and optimal analysis of an interacting quantum dot thermoelectric refrigerator

Abstract: We investigate the thermodynamic performance of a quantum-dot refrigerator consisting of a single orbital interacting quantum dot embedded between two electron reservoirs at different temperatures and chemical potentials. Based on the quantum master equation the expressions for the cooling power and the coefficient of performance are derived. The characteristic curves between the cooling power and the coefficient of performance are plotted, and the optimal regions of the performance parameters are determined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
(43 reference statements)
0
3
0
2
Order By: Relevance
“…486 Other calculations for an interacting QD thermoelectric refrigerator based on the quantum master equation showed that a high maximum cooling power, Q max , of ∼0.43 J S −1 and a high COP of >0.09 can be achieved by tuning the Coulomb interaction U. 487 These calculated results can provide theoretical guidelines for the design and operation of the practical QD-based thermoelectric devices.…”
Section: Dimensional Designmentioning
confidence: 90%
“…486 Other calculations for an interacting QD thermoelectric refrigerator based on the quantum master equation showed that a high maximum cooling power, Q max , of ∼0.43 J S −1 and a high COP of >0.09 can be achieved by tuning the Coulomb interaction U. 487 These calculated results can provide theoretical guidelines for the design and operation of the practical QD-based thermoelectric devices.…”
Section: Dimensional Designmentioning
confidence: 90%
“…典型的两端量子 点热电器件是由量子点嵌入到两个具有不同温度和化 学势的电子库构成. 基于塞贝克与帕尔帖效应量子点 热电器件能够作为热机 [17,120,[143][144][145] 、热泵 [146,147] 或制 冷机 [21,[148][149][150] 实现不同的能量转换过程.…”
Section: 将可作为热机对外输出功unclassified
“…Zhang和 He [153] , Wang等人 . 2012年, Muralidharan和Grifoni [120] , Zhang等人 [149] 研究了库仑相互作用对单能级相互作用量子点装置热 电效率和制冷效率的影响. 上述研究主要关注单能级 量子点系统的热电性能, 而实际的量子点器件往往有 不止一个能级参与电子的输运, 因此研究多能级量子 点热电系统也进一步产生了许多有趣的现象 [156][157][158] .…”
Section: 将可作为热机对外输出功unclassified
“…By using the quantum master equation, the evolution of the occupation probability is described as [20][21][22][23][25][26][27] …”
Section: Quantum Dot Heat Engine In An External Magnetic Fieldmentioning
confidence: 99%
“…Muralidharan and Grifoni used nonequilibrium currents of the steady state to evaluate the performance of a thermoelectric setup through a single orbital interacting quantum dot, in which the Coulomb interaction was taken into account [24]. Zhang et al used the master equation to evaluate a spin degenerate quantum dot refrigerator in which the influence of the Coulomb interaction was considered as well [25]. Wang et al studied a quantum dot engine with two discrete energy levels, in which the Coulomb energy between the electrons in one energy level was neglected, revealing the effects of the energy level and energy space on the performance of the engine [26].…”
Section: Introductionmentioning
confidence: 99%